2012
DOI: 10.1029/2011je003816
|View full text |Cite
|
Sign up to set email alerts
|

Possible evidence of paleomarsquakes from fallen boulder populations, Cerberus Fossae, Mars

Abstract: [1] In order to differentiate between boulder avalanche deposits triggered by temperature/climate controlled melting of ice or triggered by ground shaking produced by paleomarsquakes, spatial variation in boulder size populations has been measured from High Resolution Imaging Science Experiment (HiRISE) images along Cerberus Fossae, one of the youngest fracture/graben systems on the Martian surface. The boulders have fallen from less than $500 m high fault-controlled cliffs and rolled and bounced across relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 34 publications
9
90
0
Order By: Relevance
“…However, studies by Antoine et al () suggest that endogenic heat sources might well be present within Mars associated with the Cerberus Fossae fault system. Roberts et al (), using understanding of natural seismometers on Earth, suggested that large‐magnitude marsquakes may have occurred in the recent past along Cerberus Fossae, evidenced by observations close to faults of anomalies in the density of trails left by mobilized boulders and boulder trail widths (Figures and ). Roberts et al () showed, for Cerberus Fossae, that boulder trail densities per kilometer and boulder trail widths increased systematically from background values along the strike of part of the fault system, interpreting this as possible evidence that a marsquake had produced ground shaking responsible for mobilization of the boulders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies by Antoine et al () suggest that endogenic heat sources might well be present within Mars associated with the Cerberus Fossae fault system. Roberts et al (), using understanding of natural seismometers on Earth, suggested that large‐magnitude marsquakes may have occurred in the recent past along Cerberus Fossae, evidenced by observations close to faults of anomalies in the density of trails left by mobilized boulders and boulder trail widths (Figures and ). Roberts et al () showed, for Cerberus Fossae, that boulder trail densities per kilometer and boulder trail widths increased systematically from background values along the strike of part of the fault system, interpreting this as possible evidence that a marsquake had produced ground shaking responsible for mobilization of the boulders.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al (), using understanding of natural seismometers on Earth, suggested that large‐magnitude marsquakes may have occurred in the recent past along Cerberus Fossae, evidenced by observations close to faults of anomalies in the density of trails left by mobilized boulders and boulder trail widths (Figures and ). Roberts et al () showed, for Cerberus Fossae, that boulder trail densities per kilometer and boulder trail widths increased systematically from background values along the strike of part of the fault system, interpreting this as possible evidence that a marsquake had produced ground shaking responsible for mobilization of the boulders. This study was facilitated by the advent of HiRISE imagery (High Resolution Imaging Science Experiment onboard the Mars Reconnaissance Orbiter) whose high resolution (~25‐cm pixel sizes) allowed, for the first time, observations of boulders and boulder trails from orbit, in particular the largest boulders and trails, and hence the ability to map the characteristics of boulder populations along the strike of fault systems.…”
Section: Introductionmentioning
confidence: 99%
“…In a post-Noachian Mars, we postulate that seismicity could play an important role in coarse sediment transport on hillsides, as it does in the Atacama Desert today. This speculation is strongly supported by the observations of the Cerberus Fossae graben system on Mars by Roberts et al (2012), who presented convincing evidence that the origin of the boulder fi elds in this region is probably seismic, given the strong correlation of large boulders with areas of recent surface faulting. The combined evidence from the Atacama Desert and Cerberus Fossae on Mars suggests that seismicity is a major agent of transport of coarse sediment on hyperarid Earth and post-Noachian Mars.…”
Section: Larger Role Of Seismicity In Dry Worldsmentioning
confidence: 58%
“…In the absence of seismometric data, active seismicity on Mars can only be inferred indirectly from geologic and surface morphology, such as fault scarps in the Cerberus Fossae Region. Rockfalls in this region may also have a seismic origin (Roberts et al, 2012). Based on our experience in the Atacama, we Fig.…”
Section: Earthquakes and Surface Processes In The Atacama Desertmentioning
confidence: 98%
“…For example, seismicity has probably been significantly contributing to post-Noachian Mars landscape change (e.g. Roberts et al, 2012), and may be as important on other virtually waterless worlds of our solar system, such as the Earth's Moon and many asteroids. In this paper we expand significantly on the work by Quade et al (2012) by combining published cosmogenic isotope measurements and field observations with new measurements and observations to understand the formation and evolution of the Atacama boulder fields.…”
Section: Introductionmentioning
confidence: 99%